Acute Onset of Impaired Consciousness: Diagnostic Evaluation in the Emergency Department. - Weiglein, T.; Zimmermann, M.; Niesen, W. D.; Hoffmann, F.; Klein, M. (Deutsches Ärzteblatt International, 2024)
Background: Mortality in patients with acute onset of impaired consciousness is high: as many as 10% do not survive. The spectrum of differential diagnoses is wide, and more than one underlying condition is found in one-third of all cases. In this article, we describe a structured approach to patients with acute onset of impaired consciousness in the emergency department. Methods: This review is based on pertinent articles retrieved by a selective search of PubMed and on the AWMF guidelines on the most common causes of impairment of consciousness. Results: Impairments of consciousness are classified as quantitative (reduced wakefulness) or qualitative (abnormal content of consciousness). Of all such cases, 45-50% have a primary neurological cause, and approximately 20% are of metabolic or infectious origin. Some cases are due to intoxications, cardiovascular disorders, or psychiatric disorders. Important warning signs ("red flags") in acute onset of impaired consciousness are a hyperacute onset, pupillomotor disturbances, focal neurologic deficits, meningismus, headache, tachycardia and tachypnea (with or without fever), muscle contractions, and skin abnormalities. Patients with severely impaired consciousness should be initially treated in the shock room according to the ABCDE scheme. Conclusion: Acute onset of impaired consciousness is a medical emergency. Red flags must be rapidly recognized and treatment initiated immediately. Patients with severely impaired consciousness of new onset and uncertain cause, status epilepticus, lack of protective reflexes, or a new, acute neurologic deficit should be admitted via the resuscitation room.